Women's Health and Biomechanics Where Medicine and Engineering Meet - Brandão, Sofia; Da Roza, Thuane; Ramos, Isabel; Mascarenhas, Teresa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book focuses on particular mental and physical aspects of women's health, presenting topics concerning the pelvis and pelvic floor dysfunction and the breast during a woman's life, such as rehabilitation for pelvic and breast disorders, and the benefits of biomechanical analysis in treating these conditions. With each chapter providing a brief survey of a major research area related to the theme, the book offers an integrated overview of topics such as the bio-psycho-social model of women's health, pelvic floor evaluation in sports, the breast, pregnancy and delivery. It is a valuable resource for a wide range of readers, including researchers, graduates and professionals.      .
Improving Women´s Health via the Bio-Psycho-Social Model -- Section 1: The Young Women -- Sports and UI -- Pelvic Floor Evaluation in Sports -- Diagnostic Devices -- Section 2: The Reproductive Period of Women´s Life -- Pregnancy and Ergonomics -- The changes in Biomechanics due to Pregnancy and Parity -- Ultrasound Imaging Assessment of diastasis recti -- Biomechanical Analysis of the Damage in the Pelvic Floor Muscles During Childbirth -- Breast Imaging: from Morphology to Tissue Structure -- The Effects of Mastectomy and Reconstruction on Body Posture and Biomechanics -- The Role of Physiotherapy in Women with Breast Cancer -- Breast Implants: Far Beyond Just Aesthetic Surgery -- The Female Pelvic Floor (Dysfunction): from Clinical Practice to Biomechanics -- Imaging Female Pelvic Floor Dysfunction -- Section 3: The Older Women -- Searching for Biomechanical Tissue Properties in Pelvic Floor Dysfunction by Computational Modeling -- Pelvic Floor Dysfunction / Urinary Incontinence: Rehabilitation Treatments and the Improvement in Quality-of-Life -- The Role of Ultrasound Imaging of Musculotendinous Structures in the Elderly Population -- Mental Health and Physical Activity.  .
Keywords: Mechanics, Applied; Solids; Mechanical engineering; Biomedical engineering; Radiology; Gynecology .; Sports medicine; Solid Mechanics; Mechanical Engineering; Biomedical Engineering and Bioengineering; Radiology; Gynecology; Sports Medicine